Race, Employment Discrimination, and State Complicity in Wartime Canada, 1939-1945 - Patrias, Carmela (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2007)
Abstract The study that the crisis of war reinforced pre-existing social and economic inequality based on racist views and practices. War-induced anxieties intensified suspicion of “foreigners” — a term which encompassed large numbers of Canadian-born and naturalized people of Japanese, central, eastern, and southern European descent and Jews — as unpatriotic, disloyal, radical, and incapable of becoming truly Canadian. The war also brought sharply into focus and even intensified racist assumptions that African Canadians, eastern and southern Europeans, and Native people were suitable only for menial jobs; that Jewish, Chinese, and Japanese Canadians were economically aggressive; and that Jews in particular were given to shady practices. Such racist stereotypes in turn legitimized the ongoing marginalization of these minorities in the workforce. The state colluded in racist practices. To be sure not all state officials or all Canadians were racist, but the pragmatism that informed official complicity with employment discrimination underscores the pervasiveness of racism in wartime Canada. State officials — some of whom held racist ideas — were willing to accept employers’ and workers’ racist preferences because they believed that to do otherwise would create social unrest and disrupt war industries. Moreover, officials found that the relegation of minority groups such as Chinese Canadians, Japanese Canadians, and Native people to menial work offered the important benefit of filling jobs that Canadians with wider options avoided.